2022
DOI: 10.1192/j.eurpsy.2022.2303
|View full text |Cite
|
Sign up to set email alerts
|

The network structure of ICD-11 adjustment disorder: A comparison of clinical and nonclinical samples

Abstract: Background International Classification of Diseases, 11th revision (ICD-11) adjustment disorder (AjD) is characterized by two main symptom clusters: preoccupation with the stressor and failure to adapt to the stressor. The network analytic approach provides important information on the structural validity of a disorder and reveals which symptoms are most prominent. To date, no study compared the network structure of AjD symptoms in clinical and nonclinical samples, which could potentially inform our under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…Strong associations were observed between individual preoccupation symptoms and between failure-to-adapt symptoms, but weaker associations between these core symptom clusters. This confirms our hypothesis and replicates earlier network studies in non-clinical 12 and clinical samples 29 and confirms the structure of adjustment disorder suggested in ICD-11. We report the first study to show that overall connectivity of adjustment disorder symptoms remained equally strong over 3 months, further confirming the validity of the adjustment disorder symptoms in ICD-11.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Strong associations were observed between individual preoccupation symptoms and between failure-to-adapt symptoms, but weaker associations between these core symptom clusters. This confirms our hypothesis and replicates earlier network studies in non-clinical 12 and clinical samples 29 and confirms the structure of adjustment disorder suggested in ICD-11. We report the first study to show that overall connectivity of adjustment disorder symptoms remained equally strong over 3 months, further confirming the validity of the adjustment disorder symptoms in ICD-11.…”
Section: Discussionsupporting
confidence: 92%
“…Strong associations were observed between individual preoccupation symptoms and between failureto-adapt symptoms, but weaker associations between these core symptom clusters. This confirms our hypothesis and replicates Adjustment disorder symptoms and probable diagnosis earlier network studies in non-clinical 12 and clinical samples 29 and confirms the structure of adjustment disorder suggested in ICD-11.…”
Section: Network Structuresupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the meta-analysis conducted by Mitchell et al also found a signi cant association between AjD and female sex (7). This association has also been found in clinical samples of patients from the UK and nonclinical participants from Switzerland (32). Similarly, a study conducted by Abumadini on Saudi patients visiting psychiatric outpatient clinics found that 69.6 percent of participants who had a diagnosis of AjD were women (33).…”
Section: Discussionmentioning
confidence: 71%
“…Chronic diseases can represent such a stressor (De Ridder et al, 2008 ). ICD-11 adjustment disorder has two core symptoms: preoccupations and failure to adapt (Levin et al, 2022 ; Maercker & Lorenz, 2018 ). In the case of cardiac disease, preoccupations can comprise repeated, afflicting, and involuntary thoughts about the disease or its consequences (e.g.…”
Section: Theoretical Backgroundmentioning
confidence: 99%